MAKNA TANDA DALAM IKLAN CERDIKIAWAN GOJEK INDONESIA - Andi Puteri Mangkawani; Nensilianti Nensilianti (Universitas Negeri Makassar, 2020)
The Meaning of Signs in Gojek Indonesia Cerdikiawan. This research aims to describe the meaning of the sign in advertising cerdikiawan gojek Indonesia. The data obtained are qualitative data, namely all forms of connecting the verbal or nonverbal statement into icon, index, and symbol contained in ads cerdikiawan gojek Indonesia. Sources of data obtained through the youtube page Gojek Indonesia. The theory used is the theory of sign systems, and semiotic approach belonged to Charles Sanders Peirce. Qualitative descriptive method is used to determine the overall meaning cerdikiawan ads gojek Indonesia. The results obtained show that: (1) the meaning of the sign messages in the Indonesian Cerdikiawan Gojek adverts resulted in Cerdikiawan's contemporary vocabulary represented from present life;dan (2) the taxation and narration presented in the advertisements became a satire for today's society.